Brands using historical references: a consumers' perspective. Issue 2 (March 2018) - Pecot, Fabien; Barnier, Virginie
Abstract While existing literature on brand heritage focuses on corporate perspectives, this paper investigates the gap between intended and perceived heritage. Two sequential qualitative studies were performed: the preliminary study is based on observation and enables the selection of 27 fast-moving consumer brands using historical references that are explicit for consumers; the main study is composed of 25 semi-structured interviews of consumers in order to analyse their interpretations. Results show that consumers know little about parent companies behind brands. However, they imagine that companies are seeking a compromise between an ideal tradition and a necessary modernity. Finally, they also distinguish different strategies in the management of temporality. Results outline the critical role of the consumers and enable to distinguish two types of brands—familiar and aristocratic ones—and to formulate two distinct sets of recommendations for them based on the use of historical references.